The Link Between Autonomic Nervous System and Rheumatoid Arthritis: From Bench to Bedside - Ingegnoli, Francesca; Buoli, Massimiliano; Antonucci, Flavia; Coletto, Lavinia Agra; Esposito, Cecilia Maria; Caporali, Roberto (Frontiers in Medicine, 2020)
Neuronal stimulation is an emerging field of research focused on the management and treatment of various diseases through the reestablishment of physiological homeostasis. Electrical vagus nerve stimulation has recently been proposed as a revolutionary therapeutic option for rheumatoid arthritis (RA) in combination with or even as a replacement for conventional and biological drugs. In the past few years, disruption of the autonomic system has been linked to RA onset and activity. Novel research on the link between the autonomic nervous system and the immune system (“immune-autonomics”) has paved the way for the development of innovative l RA management strategies. Clinical evidence supports this approach. Cardiovascular involvement, in terms of reduced baroreflex sensitivity and heart rate variability–derived indices, and mood disorders, common comorbidities in patients with RA, have been linked to autonomic nervous system S dysfunction, which in turn is influenced by increased levels of circulating pro-inflammatory cytokines. This narrative review provides an overview of the autonomic nervous system and RA connection, discussing most of the common cardiac and mental health–related RA comorbidities and their potential relationships to systemic and joint inflammation.